Avicenna’s Integrative Psychological and Behavioral Approaches to Pain Management - Mohammad Radmehr; Habib Zakeri; Aliasghar Karimi (Journal of Research on History of Medicine)
Avicenna, known as Ibn Sina, was a pioneering physician and philosopher whose magnum opus, The Canon of Medicine, synthesized knowledge from Greek, Persian, and Indian medical traditions, creating a comprehensive approach and emphasizing the balance of mind, body, and environment. His theories on pain management extended beyond physical remedies, incorporating psychological and behavioral techniques, such as distraction, music therapy, and environmental adjustments. Avicenna recognized the influence of emotional and mental states on physical health, suggesting that pain perception could be shaped by factors such as stress and emotional well-being. This understanding aligns closely with contemporary pain management strategies, including cognitive-behavioral therapy (CBT), mindfulness, and psychosomatic medicine, which also acknowledge the mind-body connection. The article underscores the enduring significance of Avicenna’s holistic philosophy, especially as integrative and complementary medicine gains traction in treating chronic pain conditions. By analyzing Avicenna’s approaches in a historical context and comparing them to modern interdisciplinary methods, this review highlights the value of combining ancient wisdom with current scientific insights to create more comprehensive, patient-centered pain management strategies. Avicenna’s legacy continues to inform and inspire today’s holistic health practices, underscoring the timeless relevance of his integrative approach to well-being.